Efficient Reservoir Operation in an Arid Region with Extreme Hydrologic Flows: A Case Study, Oman's Largest Dam - Karimi, Akbar; Nematollahi, Banafsheh; Nikoo, Mohammad Reza (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
Wadi Dayqah dam (WDD) is still not operating, and its operation targets are not yet fixed. Arid hydrology and the presence of new users require a new look at this dam's operation plan. The updated and optimal operation plan of WDD is the central research gap about this dam. In this study, to fill this gap, Water Evaluation and Planning (WEAP) is used to model the system and six scenarios, including the reference target of 35 MCM per year suggested goal that considers different operation targets as well as a modification to water system configuration by the addition of an upstream dam is suggested. This model is validated and used for 37 years of historical flow. Results show that the reference scenario is less than 55%, and an annual goal of 15 MCM has a maximum of 85% supply reliability. Adding a 20 MCM upstream dam can increase reliability by 5%. It is recommended that to enhance the economic aspects of the dam, suitable energy generation schemes are studied with unique configurations, such as pumped-storage hydro, as well as studying the other sizes of upstream dams that can contribute more to water distribution and energy generation.